A review of optimisation techniques used in the composite recycling area: state-of-the-art and steps towards a research agenda - Liu, Ying; Farnsworth, Michael; Tiwari, Ashutosh (Elsevier, 2016)
The increased use of carbon fibre and glass fibre reinforced polymer in industry coupled with restrictions on landfill disposal has resulted in a need to develop effective recycling technologies for composites. Currently, mechanical, thermal and chemical approaches have been use to recycle composites. This paper seeks to examine the applications of engineering optimisation techniques in the composite recycling and re-manufacturing processes and their relevant systems, providing an overview of state-of-the-art. This paper is based on a comprehensive review of literature covering nearly all the research papers in this area. These papers are analysed to identify current trends and future research directions. The composite recycling is a relatively new area, and the modelling and optimisation work for composite recycling and re-manufacturing techniques and their relevant systems is still in its infancy. Currently, the optimisation work developed in composite recycling mainly focus on the applications of design of experiments methods. These approaches have been applied to improve the quality of recyclates such as carbon fibres. Some of the soft-computing algorithms have been applied to optimise the re-manufacturing at the system level. Based on the existing research, the area of optimisation for composite recycling and re-manufacturing haven't been well explored despite the fact that many opportunities and requirements for optimisation exist. This means significant amount of modelling and optimisation work is required for the future research. More significantly, considering optimisation at the early stage of a system development is very beneficial in terms of the long term health of the composite recycling industry.
Keywords: Composite; Recycling; Optimisation